Training on the Implementation of Accounting for MSME Business at SMK N 1 Tempel - Ayuntari, Chivalrind Ghanevi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This activity provide knowledge about accounting for MSMEs for SMK N 1 Tempel students who will take part in the Field Work Practice program. Large number of MSME who have difficulties in financial recording and calculating Cost of Goods Sold. Thus, they have difficulty in assessing whether their business is profit or loss-making. The purpose of this community service is to provide knowledge to students while FWP in MSMEs about accounting and simple bookkeeping skills so that they are able to prepare financial reports. This activity is carried out using a training method consisting of preparation, assessment, implementation, and evaluation stages. The results achieved from this activity are delivering knowledge and bookkeeping skills, calculating COGS and preparing MSME financial reports.